واقع الإيرادات البلدية ومجالات صرفها: دراسة حالة بلدية سلفيت - عاصي, هبة (هبة محمود عاصي, 2018)
The present study aimed at identifying the reality of municipal revenues and the areas of their disbursement: a case study of Salfit municipality, and the importance of this subject and because of the lack of dealing in studies - according to the researcher - it was necessary to shed light on it, and to indicate the types of municipal revenues and areas of use, Community. The descriptive approach and the analytical approach were followed. The study dealt with models, theories and previous studies that included the literature of the subject, and formed the theoretical part of the study, which included a description of the situation and the Palestinian reality. The study population is from all the municipalities in Palestine. The study used the municipality of Salfit as a sample and relied on the financial statements which include the budgets, which show the revenues and expenditures. In addition to the interviews with the administrative staff of the municipality of Salfit to review their views on the subject of the study. The financial reports of the municipality were reviewed during the period of study and comparison between 2005 and 2016. The study found that most of the expenditure is mostly directed by the donor countries. In addition, the study concluded that the effectiveness of methods and methods of revenue collection affects The majority of the revenues of Salfit municipality are unsustainable economy, most of which are services, do not invest in the establishment of economic projects that promote the local community or contribute to the Palestinian economy in general, and in the light of the results of the study, N the reality of the municipality of Salfit is the reality of ambition, despite the difficulties they are facing, there is a desire of the municipality to achieve better services, more effective financial and development. The study also showed that the financing of Salfit municipality is primarily external financing, which depends on donors. The increases that occur from year to year are due to different ways of collecting citizens, their effectiveness and efficiency.
Keywords: واقع الإيرادات البلدية ومجالات صرفها: دراسة حالة بلدية سلفيت